Analisis Vegetasi Tumbuhan Tingkat Pohon di Kawasan Hutan Pendidikan dan Pelatihan Universitas Muhammadiyah Bengkulu - Pariyanto Pariyanto; Kiki Fatmawati; Nourma Evianti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This study aims to determine the analysis of plant vegetation tree level area of forest education and training University of Muhammadiyah Bengkulu, according to a study conducted in Januari to February 2018 in the Forest of education and training University of Muhammadiyah Bengkulu in specimen collection is done by putting in a systematic plot, with a plot size of 10 x10 m, the distance between the plot of 20 m, the total number of plots 35 plots. Based on identification obtained 19 Family consisting of 30 species with the number of 205 people, with Importance Value Index (IVI) is highest in Shorea gobbosa with IVI is 29.57% with relative kerpatan 7.80%, the value of the relative frequency of 7.56% and the relative dominance of 14.21%. whereas the type which has important value index (IVI) is lowest for the Lansium domesticum, with important value index kerpatan 1.08% with a relative value of 0.49%. the value of the relative frequency of 0.44% and 0.15% relative dominance values. The diversity index type at all levels have value diversity index +1,392.